Comparative Study of Efficacy and Adverse Effects of Metformin Plus Empagliflozin Versus Metformin Plus Sitagliptin in Diabetes Mellitus Type II Patients - Uzma Batool; Abdullah (Indus Journal of Bioscience Research, 2025)
Introduction: This study aims to compare the efficacy and adverse effects of metformin combined with empagliflozin versus metformin combined with sitagliptin in Type II DM patients in Pakistan. Given the rising prevalence of diabetes in Pakistan, evaluating these widely used combination therapies in a local population is essential for optimizing treatment strategies. This research will provide valuable insights into glycemic control and safety profiles in a population with unique genetic, dietary, and lifestyle factors, which are often underrepresented in global studies. Materials and Procedures: This single-blinded RCT enrolled 112 patients aged 35–65 with HbA1c 7–9%, diabetes >1 year. Patients were randomized into two groups: Group A received Metformin plus Empagliflozin, and Group B received Metformin plus Sitagliptin. Exclusions included irregular medication, prior hypoglycemic use, high creatinine, or glucose-altering drugs. HbA1c was measured monthly; compliance and side effects were monitored. Results: In my research, patients treated with metformin + empagliflozin had a higher likelihood of being in the metformin + empagliflozin group than those treated with metformin + sitagliptin (48.21% vs. 26.79%, respectively) if their HbA1c was under 7%. Side effects with empagliflozin are less than sitagliptin i.e. diarrhea (3.57% vs 8.93%), rash (0.0% vs 5.36%), hypoglycemia (12.50% vs 16.07%), UTI (0.0% vs 7.14%) and increased urination (19.64% vs 10.71%) respectively. Conclusion: When used in conjunction with metformin, SGLT-2 inhibitors are just as safe, effective, and well-tolerated in individuals with Type 2 diabetes mellitus as DPP4 inhibitors.